Zanubrutinib monotherapy for patients with treatment naïve chronic lymphocytic leukemia and 17p deletion - Tam, Constantine S; Robak, Tadeusz; Ghia, Paolo; Kahl, Brad S; Walker, Patricia; Janowski, Wojciech; Simpson, David; Shadman, Mazyar; Ganly, Peter S; Laurenti, Luca; Opat, Stephen; Tani, Monica; et al. (Haematologica, 2021)
Patients with chronic lymphocytic leukemia or small lymphocytic lymphoma whose tumors carry deletion of chromosome 17p13.1 [del(17p)] have an unfavorable prognosis and respond poorly to standard chemoimmunotherapy. Zanubrutinib is a selective next-generation Bruton tyrosine kinase inhibitor. We evaluated the safety and efficacy of zanubrutinib 160 mg twice daily in treatment-naïve patients with del(17p) disease enrolled in a dedicated, nonrandomized cohort (Arm C) of the phase 3 SEQUOIA trial. A total of 109 patients (median age, 70 years; range, 42 - 86) with centrally confirmed del(17p) were enrolled and treated. After a median of 18.2 months (range, 5.0 - 26.3), seven patients had discontinued study treatment due to progressive disease, four due to an adverse event, and one due to withdrawal of consent. The overall response rate was 94.5% with 3.7% of patients achieving complete response with or without incomplete hematologic recovery. The estimated 18-month progression-free survival rate was 88.6% (95% CI, 79.0 - 94.0) and the estimated 18-month overall survival rate was 95.1% (95% CI, 88.4 - 98.0). Most common all-grade adverse events included contusion (20.2%), upper respiratory tract infection (19.3%), neutropenia/neutrophil count decreased (17.4%), and diarrhea (16.5%). Grade ≥ 3 adverse events were reported in 53 patients (48.6%), most commonly neutropenia (12.9%) and pneumonia (3.7%). An adverse event of atrial fibrillation was reported in three patients (2.8%). Zanubrutinib was active and well tolerated in this large, prospectively enrolled treatment cohort of previously untreated patients with del(17p) chronic lymphocytic leukemia/small lymphocytic lymphoma. This trial was registered at ClinicalTrials.gov as #NCT03336333.
Keywords: Piperidines; Leukemia, Lymphocytic, Chronic, B-Cell; Pyrazoles; Pyrimidines; Aged; lidé; pyrazoly; senioři; chronická lymfatická leukemie; piperidiny; pyrimidiny; Humans